Study on diversity, nitrogen-fixing capacity, and heavy metal tolerance of culturable Pongamia pinnata rhizobia in the vanadium-titanium magnetite tailings - Shen, Tian; Jin, Ruimin; Yan, Jing; Cheng, Xiran; Zeng, Lan; Chen, Qiang; Gu, Yunfu; Zou, Likou; Zhao, Ke; Xiang, Quanju; Penttinen, Petri; Ma, Menggen; et al. (Frontiers in Microbiology, 2023)
The diversity, nitrogen-fixing capacity and heavy metal tolerance of culturable rhizobia in vanadium (V) - titanium (Ti) magnetite (VTM) tailings is still unknown, so this study focused on the diversity of rhizobia in symbiotic relationship with Pongamia pinnata grown in the extreme barren VTM tailings contaminated with a variety of metals. P. pinnata plants were cultivated in pots containing the VTM tailings until root nodules were formed. Among 57 rhizobia isolated from these nodules, only twenty strains showed different levels of tolerance to copper (Cu), nickel (Ni), manganese (Mn) and zinc (Zn), especially strains PP1 and PP76 showing high tolerance against these four heavy metals. Based on the phylogenetic analysis of 16S rRNA and four house-keeping genes (atpD, recA, rpoB, glnII), twelve isolates were identified as Bradyrhizobium pachyrhizi, four as Ochrobactrum anthropic, three as Rhizobium selenitireducens and one as Rhizobium pisi. Some rhizobia isolates showed a high nitrogen-fixing capacity and promoted P. pinnata growth by increasing nitrogen content by 10%-145% in aboveground plant part and 13%-79% in the root. Rhizobium pachyrhizi PP1 showed the strongest capacity of nitrogen fixation, plant growth promotion and resistance to heavy metals, which provided effective rhizobia strains for bioremediation of VTM tailings or other contaminated soils. This study demonstrated that there are at least three genera of culturable rhizobia in symbiosis with P. pinnata in VTM tailings. Abundant culturable rhizobia with the capacity of nitrogen fixation, plant growth promotion and resistance to heavy metals survived in VTM tailings, indicating more valuable functional microbes could be isolated from extreme soil environments such as VTM tailings.